Current situation and future topics of road traffic noise problems in Japan - TACHIBANA, H. (Archives of Acoustics, 1999)
Regarding the road traffic noise problem in Japan, the current situation and the administrative countermeasures are reviewed. Next, from the technological viewpoint, the progress of regulation of the vehicle noise emission and various kinds of noise reduction technologies are introduced. Regarding the assessment and prediction methods for road traffic noise, the historical course in Japan and future problems are briefly described. Lastly, as future subjects, not only technical developments but also administrative and socio-psychological measures are discussed.